2010
DOI: 10.1163/156853710x497220
|View full text |Cite
|
Sign up to set email alerts
|

Language and Experience Influence Children's Biological Induction

Abstract: Children's reasoning about biological concepts is infl uenced not only by their experiences in the natural world and in their classrooms, but also by the way that these concepts are named. In English, 'animal' can refer either to (a) exclusively non-human animals, or (b) all animate beings (human and non-human animals). In Indonesian, this category of animate beings has no dedicated name. Here, we ask whether this diff erence in naming has consequences for children's reasoning about humans and non-human animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Prior research has found that differences in early opportunities for direct experience with animals (e.g., Anggoro et al, 2010;Medin et al, 2010;Ross et al, 2003;Unsworth et al, 2012; and conversations with parents (e.g., Tarlowski, 2006) impact early biological reasoning. Especially for urban children who may have few opportunities to encounter live animals, zoos and museums are an ideal setting for exploring the content of parent-child interaction about animals (Allen, 2002;Ash, 2003;Kisiel et al, 2012;Kopczak et al, 2015;Patrick & Tunnicliffe, 2013;Rigney & Callanan, 2011;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has found that differences in early opportunities for direct experience with animals (e.g., Anggoro et al, 2010;Medin et al, 2010;Ross et al, 2003;Unsworth et al, 2012; and conversations with parents (e.g., Tarlowski, 2006) impact early biological reasoning. Especially for urban children who may have few opportunities to encounter live animals, zoos and museums are an ideal setting for exploring the content of parent-child interaction about animals (Allen, 2002;Ash, 2003;Kisiel et al, 2012;Kopczak et al, 2015;Patrick & Tunnicliffe, 2013;Rigney & Callanan, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…More recent work focusing on cultural comparisons suggests that differences in experience, language, and environment all influence the development of children's domainspecific biological reasoning (e.g., Anggoro, Medin, & Waxman, 2010;Ross, Medin, Coley, & Atran, 2003;. Even before formal schooling begins, children's folkbiological reasoning reflects beliefs about nature and biology that are specific to their culture (Unsworth et al, 2012;Waxman, Medin & Ross, 2007).…”
Section: Children's Biological Knowledge Developmentmentioning
confidence: 99%
“…A line of cognitive research has produced substantial evidence supporting the claim that children understand the concept of ANIMAL early in development (e.g., Pascalis, de Haan, & Nelson, 2002;Johnson, Slaughter, & Carey, 1998) and that children are exposed to naming practices of biological entities that support the development of biological concepts (Gelman, 2003;Graham, Kilbreath, & Welder, 2004;Waxman & Markow, 1995). However, there is an important complicating factor in this line of research that points to the value of situative perspectives: The noun animal is polysemous, that is, the concept animal can have multiple meanings (Anggoro, Medin, & Waxman, 2010a). Medin, Lee, and Bang (2014), exploring this issue from a cross-cultural view, using language as a proxy, explained that for speakers of English, "animal can refer either to an inclusive concept, including all animate beings (as in "Animals have babies"), or it can refer to a more restricted concept that includes nonhuman animals but excludes humans (as in "Don't eat like an animal").…”
Section: Concepts Of Interest Ranged From What Kinds Of Basic Ideas Cmentioning
confidence: 99%
“…The patterns of induction reflect individuals' concepts of animals and living things. These differences in reasoning patterns reflect culturally specific naming practices as well as biologically relevant formal and informal learning experiences (Anggoro, Medin, & Waxman, 2010). Thus, we may find differences in reasoning patterns between children who have experience with pets and those who do not even though they are receiving the same culturally relevant biological instruction.…”
Section: Introductionmentioning
confidence: 94%